Association between Growth Hormone-Insulin-Like Growth Factor-1 Axis Gene Polymorphisms and Short Stature in Chinese Children. (4th March 2018) - Zhang, Yanhong; Zhang, Mei; Chu, Yuntian; Ji, Baolan; Shao, Qian; Ban, Bo
Abstract : Objective . This study was designed to analyze the association between the growth hormone-insulin-like growth factor-1 (GH-IGF-1) axis gene polymorphisms and short stature in Chinese children. Methods . 181 growth hormone deficiency (GHD) patients and 206 normal stature controls were enrolled to attend this study. Five single-nucleotide polymorphisms in the GH receptor (GHR) and 5 SNPs within the GH-signaling pathway were genotyped by matrix-assisted laser desorption/ionization time of flight mass spectrometry. We conducted an association study between these SNPs and the risk of developing short stature. Linkage disequilibrium analysis was performed using Haploview software and the associations of the SNPs frequencies with short stature were analyzed using X 2 tests. Results . No significant difference was found in gender, weight, height, and BMI between the GHD and control groups, except that the age of GHD group was older than the control one. Allele and genotype frequencies were consistent with those expected from Hardy-Weinberg equilibrium. Compared with the controls, heterozygous genotype frequencies (CT) of rs12515480 and rs6873545 of GHR gene were significantly lower. Genotype frequencies of the other 8 SNPs did not show significant difference between these two groups. Considering a dominant model, an OR < 1 was observed for genotypes rs12515480 (OR = 0.532, P = 0.019 ) and rs6873545 (OR = 0.587, P = 0.017 ). Conclusions . The heterozygous genotypes of rs12515480 and rs6873545 of GHR gene were associated with decreased risk of GHD in Chinese children.